Free Groin Flap: Innovative Approaches for Soft Tissue Defect Reconstruction - Mohd. Altaf Mir; Jaya Jain (Key Flaps in Plastic Surgery, 2023)
This book chapter presents a case report and discussion on the use of the free groin flap for reconstructive surgery in a patient with a posttraumatic soft tissue defect of the dorsum and first web of the right hand, along with the amputation of the index finger. The case presentation describes the preoperative condition and the need for reconstruction. The surgical intervention involved debridement and reconstruction using a free groin flap, completely detached from the donor area. The operative procedure included wound debridement, marking of the free contralateral groin flap, flap elevation, and reconstruction of the soft tissue defect. The flap was transferred to the defect site after vascular anastomosis, with primary closure of the donor site. The postoperative period remained uneventful, and satisfactory results were observed during follow-up examinations. The discussion section introduces the free groin flap technique as a valuable reconstructive option for large soft tissue defects, particularly in the head and neck region. The surgical techniques are described, including patient evaluation and planning, flap design and marking, donor site preparation, flap transfer with microvascular anastomosis, and flap shaping and closure. The advantages of the technique, such as robust blood supply, adequate tissue volume, versatility, and minimized donor site morbidity, are highlighted. The limitations, including the need for surgical expertise and resources, consideration of vascular anatomy, and potential donor site morbidity, are also discussed. The abstract emphasizes the significance of the free groin flap technique in reconstructive surgery, particularly in cases of large soft tissue defects in the head and neck region. It highlights the importance of meticulous surgical planning, microsurgical expertise, and detailed preoperative evaluation to achieve successful outcomes and minimize complications. By understanding the principles and considerations of the free groin flap technique, surgeons can effectively address complex defects and provide functional and aesthetically pleasing reconstructions for their patients.